The Meaning of Forgiveness in Transgender and Its Implications in Guidance and Counseling - Yuliana, Tria Mustika; Puji Sugiharto, Dwi Yuwono; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2022)
Forgiveness is a positive attitude that helps transgender people to live their lives as a minority in a common society. Thus, this study was focused on determining the meaning of transgender people forgiveness and its implication for guidance and counseling. The study used a qualitative approach with a phenomenology design and obtained data from komunitas pewaris (transgender people community in Semarang City) represented by three people. Once the data were collected, interpretative phenomenological analysis (IPA) was carried out. Findings indicated that the forgiveness in transgender people was caused by a series of events, such as regret, self-mediation, and emotional control. Moreover, individuals’ perception was found significant in transgender people forgiveness.